Why is African Trade so Limited? - Bao, Nguyen Duc; Bouët, Antoine (VNU JOURNAL OF ECONOMICS AND BUSINESS, 2022)
This paper studies the determinants of the low participation of African countries to international trade. We point out the under-trading status of Africa, then we estimate a gravity equation in order to identify the determinants of trade in general. As we characterize the level of these explanatory variables in Africa as compared to the rest of the world, we identify the main variables behind the low participation of Africa to trade in general. Usual gravity factors play an important role, but we show that non-tariff measures and the quality of infrastructure and institutions are important. Import duties does not significantly impede African exports. We test the impact on African countries’ exports of a counterfactual scenario where infrastructure and institution variables in African countries are changed to the world average and conclude that the most important leverage effect to be expected from investment in infrastructure would be from mobile cellular telephone subscriptions. If we consider only countries where exports are positively affected, this counterfactual exercise implies a change by 31.0% of national exports on average by African country. While this result is interesting it has to be considered with caution since the exact form of the relation between trade and mobile cellular telephone subscriptions is largely unknown.